2009
DOI: 10.1080/08958370802672883
|View full text |Cite
|
Sign up to set email alerts
|

Asian sand dust aggravates allergic rhinitis in guinea pigs induced by Japanese cedar pollen

Abstract: Asian sand dust (ASD) contains microbial materials, sulfate (SO(4)(2-)), and nitrate (NO(3)(-)), and is derived from air pollutants in East China. ASD reportedly causes adverse respiratory health effects; a case in point is aggravated allergen-associated experimental lung eosinophilia. Guinea pigs were administered normal saline (control), ASD (0.3 mg/animal), ASD (0.6 mg/animal), Japanese cedar pollen (JCP) (0.2 mg/kg body weight), JCP + ASD (0.3 mg/animal), or JCP + ASD (0.6 mg/animal), into their nasal cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Epidemiological studies have shown that Asian dust increases hospitalizations and emergency visits because it exacerbates asthma (Kanatani et al, 2010;Yang et al, 2005), allergic rhinitis (Chang et al, 2006) conjunctivitis (Yang, 2006) and contact dermatitis (Otani et al, 2012), and it decreases the peak expiratory flow values (Park et al, 2005;Watanabe et al, 2011). These findings are supported by some experiments with laboratory animals: Asian sand dust inhalation enhanced allergen-induced airway inflammation in mice and in guinea pigs (Hiyoshi et al, 2005;Ichinose et al, 2008;Lei et al, 2004) and allergic rhinitis in rats (Ichinose et al, 2009). …”
Section: Introductionsupporting
confidence: 72%
“…Epidemiological studies have shown that Asian dust increases hospitalizations and emergency visits because it exacerbates asthma (Kanatani et al, 2010;Yang et al, 2005), allergic rhinitis (Chang et al, 2006) conjunctivitis (Yang, 2006) and contact dermatitis (Otani et al, 2012), and it decreases the peak expiratory flow values (Park et al, 2005;Watanabe et al, 2011). These findings are supported by some experiments with laboratory animals: Asian sand dust inhalation enhanced allergen-induced airway inflammation in mice and in guinea pigs (Hiyoshi et al, 2005;Ichinose et al, 2008;Lei et al, 2004) and allergic rhinitis in rats (Ichinose et al, 2009). …”
Section: Introductionsupporting
confidence: 72%
“…Wantanabe [85] reported that 11%-22% of patients with asthma experienced worsening of lower respiratory tract symptoms on dust storm days. Some studies noted that pollen could augment the influence of desert dust on the morbidity of asthma and rhinitis [86][87][88].…”
Section: Desert Dust Associated With Asthma and Rhinitismentioning
confidence: 99%
“…Ichinose et al (2008b) first reported that exposure to Asian sand dust to OVA-sensitized mice enhanced allergen challenge-induced asthmatic responses including lung eosinophilia, Th2 cytokine and chemokine production in the lungs. More interestingly, they (Ichinose, 2009). However, the relationship between Asian sand dust and health problems remains inconclusive, and further epidemiological and experimental studies are required.…”
Section: Asian Sand Dustmentioning
confidence: 99%